Concurrent Radiosurgery and Immune Checkpoint Inhibition: Improving Regional Intracranial Control for Patients With Metastatic Melanoma. (March 2019) - Murphy, Blair; Walker, Joshua; Bassale, Solange; Monaco, Debra; Jaboin, Jerry; Ciporen, Jeremy; Taylor, Matthew; Dai Kubicky, Charlotte
Abstract : Objectives: The anti-CTLA-4 and antiprogrammed cell death-1 (PD-1) therapies have significantly improved survival of patients with metastatic melanoma. However, there is limited data regarding the interaction between immunotherapy (IT) and stereotactic radiosurgery (SRS) in patients with brain metastasis, particularly how combination therapy may affect toxicity and intracranial tumor control. Methods: We retrospectively reviewed 26 patients with metastatic melanoma who received immune check point inhibitors and SRS for brain metastasis from 2011 to 2017. We evaluated lesions receiving SRS concurrently (within 30 days) and sequentially with IT. Overall survival (OS), local control (LC), and regional progression free survival (RPFS) were determined. Results: In total, 26 patients and 90 lesions were treated using pembrolizumab, nivolumab and/or ipilimumab, sequentially, or concurrently with SRS. Median follow-up was 18.9 months (range, 4.9 to 62.3 mo). Median overall survival was 26.1 months. There were 3 local failures, but no significant difference between the 2 groups. Following concurrent SRS and immunotherapy, patients had a significantly longer period of intracranial progression free survival than those treated with nonconcurrent therapy, 19 months versus 3.4 months ( P <0.0001). No grade 4-5 toxicities were observed. Conclusions: Patients with melanoma metastatic to brain treated with SRS and immune checkpoint inhibitors had favorable median survival of 26.1 months compared with historical controls. Patients receiving immunotherapy within 30 days of SRS had significantly improved regional intracranial progression free survival compared with patients receiving sequential therapy. Our findings suggest synergy between checkpoint inhibitor immunotherapy and radiosurgery. Further studies are needed to confirm these findings.